Candiduria in children and susceptibility patterns of recovered Candida species to antifungal drugs in Ahvaz - Zahra Seifi; Maryam Azish; Zahra Salehi1 Salehi; Ali ZareiMahmoudabadi; Ahmad Shamsizadeh (Society of Diabetic Nephropathy Prevention, 2013)
Background: Candiduria presents as an increasingly common nosocomial infection, which may involves urinary tract. Spectrum of disease is varying from asymptomatic candiduria to clinical sepsis. Disease is most commonly caused by Candida albicans. Objectives: The aim of the present study was to determine the frequency of candiduria in children attending Abuzar Pediatrics Hospital. Patients and Methods: Urine samples were collected from 402 patients attending to the Abuzar Pediatrics Hospital, Ahvaz. 10µl of each urine sample was cultured on CHROMagar Candida plates and incubated at 37°C. Ketoconazole, amphotericine B, clotrimazole, fluconazole, miconazole and nystatin disks were used for determination of susceptibility. Results: In the present study, 402 patients with the age range <1-14 years were sampled (59.2% males and 40.8% females). Prevalence of Candida among enrolled patients was found to be 5.2% (71.4% males and 28.6% females). In our study C. albicans was identified in 19 cases as the most common yeast followed by nine C. glabrata and one C. krusei. Urine cultures were yielded more than 10000 CFU/ml in 14.3% of the cases followed by 600-10000 CFU/ml (28.5%) and 100-600 CFU/ml (57.2%). Antifungal susceptibility testing revealed that only one isolate of C. glabrata and seven isolates of C. albicans were resistant to nystatin and ketoconazole, respectively. However, all tested isolates were resistance to fluconazole. Conclusion: Asymptomatic candiduria is relatively more prevalent among children in Ahvaz and the most common agent is C. albicans. In addition, isolated Candida species were sensitive to use antifungals, with exception to fluconazole.